Manajemen Risiko terhadap Nilai Klaim Asuransi Rangka Kapal Berdasarkan ITC (Institute Time Clause) Hull 1.10.83 Clause 280 (All Risks Comprehensive) Pada Kapal BG. TRG 06 - Muhammad Faris Putratama; Minto Basuki (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This qualitative study aims to examine the implementation of risk management in hull insurance by collecting data through interviews with the risk management staff of Asuransi Mitra Pelindung Mustika Ltd. The findings revealed that this company has applied the risk management process, including risk identification, risk analysis, risk evaluation, risk control, risk transfer through other insurance policies, monitoring, and review. The company covers losses due to fire, explosion, violent theft, piracy, accidents involving installations, collisions with aircraft or similar objects, earthquakes, volcanic eruptions, lightning strikes, accidents during loading or refuelling, boiler explosions, machinery shaft breakage, or latent defects in the machinery, hull, or frame of the insured vessel. Asuransi Mitra Pelindung Mustika Ltd. also compensates for losses due to the negligence of the captain, officers, or crew of the insured vessel, as well as the shipyard. Time to process the claim becomes a significant challenge in fulfilling the insured's rights in the claim for the BG. TRG 06 vessel because it takes up to 14 days to gather all the necessary documents. This company will cover all repair costs and labor expenses, with an estimated total value of IDR 7,611,100,000.00.